2023
DOI: 10.1021/acsapm.2c01960
|View full text |Cite
|
Sign up to set email alerts
|

Film-Formation and Binder-Free Pigment Printing of Fluorosilicone-Modified Polyacrylate/Pigment Hybrid Latex: Effect of Cross-Linking Degree

Abstract: Binder-free pigment dyeing/printing of textiles is a type of environmentally friendly and clean production technology that utilizes polymer/pigment hybrid latex. Although it has widespread use, the manner in which the nature of the hybrid latex influences the film formation and how systems can be designed to improve softness and air-permeability is still unclear. In this study, we synthesized a series of fluorosilicone-modified polyacrylate/pigment hybrid latexes to explore how cross-linking degree affects fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 53 publications
(90 reference statements)
0
0
0
Order By: Relevance
“…A similar observation was previously described in the literature for core–shell particles with different T g values in the core and shell using (meth)­acrylic acid as a comonomer and was ascribed to the soft BA/MMA core flowing out of the hard MMA shell . Something similar could also have happened in our case and if these large particles contain water or air; this inclusion can result in hazy or opaque films, , which is also observed for films from s L l , s M l , and h A l . To improve the appearance of the hazy films ( i.e., s L l , s M l , and h A l ), the films were annealed at 60 °C (prep D) and even 100 °C for 5 days.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…A similar observation was previously described in the literature for core–shell particles with different T g values in the core and shell using (meth)­acrylic acid as a comonomer and was ascribed to the soft BA/MMA core flowing out of the hard MMA shell . Something similar could also have happened in our case and if these large particles contain water or air; this inclusion can result in hazy or opaque films, , which is also observed for films from s L l , s M l , and h A l . To improve the appearance of the hazy films ( i.e., s L l , s M l , and h A l ), the films were annealed at 60 °C (prep D) and even 100 °C for 5 days.…”
Section: Resultssupporting
confidence: 90%
“…The presence of smaller particles is desirable to improve the film formation by increasing the capillary forces needed for coalescence. 86 , 87 These large particles surrounded by smaller ones are also observed using AFM ( Figure 9 c,d) and in AFM and SEM for some of the other coatings ( s L l , s M s , and h A l ); all these coatings contain a high T g macromonomer (see SI for AFM images of the other films). When considering the SEM image in more detail, we observe that these large particles seem to be hollow (see some broken particles in the SEM image in Figure 9 b).…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…Частично замененная гуаровая камедь является подходящим вариантом благодаря цвету и физическим свойствам. В работе [4] рассмотрена пигментная печать без связующего вещества. В этом исследовании синтезировали серию гибридных латексов полиакрилата и пигмента, модифицированных фторсиликоном.…”
Section: литературный обзорunclassified
“…Lu et al synthesized fluorosilica-modified polyacrylate/pigment mixed emulsions and found that the cross-linking degree of polyacrylate chains considerably influenced film formation and printing performance. The resulting films had uniformity and enhanced barrier properties and enabled improved textile pigment printing with controlled latex film-forming behavior . To enhance the printing performance of coatings, Wang et al proposed a method for preparing a hybrid pigment emulsion containing organosilicon via the copolymerization of organosilicon and acrylic monomer in a one-step miniemulsion.…”
Section: Introductionmentioning
confidence: 99%